Mathematically and biologically consistent framework for presence-absence indices of diversity. ... - Šizling, A.L.; Keil, P.; Tjørve, E.; Tjørve, K.M.C.; Žárský, J.D.; Storch, D. (Zenodo, 2023)
The upload includes the following components: (i) a basic definition of presence-absence indices commonly used in ecology, (ii) 20 theses discussing their mutual relationships and meanings, (iii) a calculator to convert any two informationally independent indices into Jaccard similarity and Simpson beta, and (iv) the data utilized in Šizling et al.'s 2023 study. Šizling, A.L., P. Keil, E. Tjørve, K.M.C. Tjørve, J.D. Žárský, and D. Storch , .202X. Mathematically and biologically consistent framework for presence-absence indices of diversity. ... : Special thanks to F. He and W. E. Kunin for their comments on the first versions, Z. Sokolíčková, E. Šizlingová for her help in the field, J. Klimešová and A. Bernard for lessons in Arctic plants, and R.K. Colwell and anonymous reviewers for insightful comments. The project was supported by the Czech Science Foundation (EXPRO 20-29554X and GA ČR 19-21341S). We used the Czech Scientific Infrastructure of the University of South Bohemia, J. Svoboda house on Svalbard – CzechPolar2 LM2015078 supported by MŠMT. PK was funded by the European Union (ERC, BEAST, 101044740). Views and opinions expressed are however those of the author(s) only and do not necessarily reflect those of the European Union or the European Research Council Executive Agency. Neither the European Union nor the granting authority can be held responsible for them. ...